2002
DOI: 10.1177/0022022102238272
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent Construal of Self and the Endorsement of Conflict Resolution Strategies in Interpersonal, Intergroup, and International Disputes

Abstract: Intergroup relations are more competitive and discordant than relations between interacting individuals. Social identity theory suggests that this discontinuity should be greatest among individuals who identify strongly with their in-group. To test this prediction, students from countries with collectivistic and individualistic cultures completed a measure of self-construal. They were then asked to identify how they would respond to a conflict, either with another individual, between their group and another gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
2
12
0
1
Order By: Relevance
“…This finding is supported by recent research [Derlega, 2002] in a test of inter-group relations and social identity theory. Here, subjects were asked how they would respond to a conflict, either with another individual, between their group and another group or between their country and another country.…”
Section: Group Inter-relationshipsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding is supported by recent research [Derlega, 2002] in a test of inter-group relations and social identity theory. Here, subjects were asked how they would respond to a conflict, either with another individual, between their group and another group or between their country and another country.…”
Section: Group Inter-relationshipsupporting
confidence: 81%
“…* Territoriality [Weller, 1985] o Presence of other like-0 Fatigue [Berk, 1974] " Presence of agitator minded [Berk, 1974] [Feinberg, 1988] 0 Proximity to like minded a Disappointment * Presence of police [Berk, 1974] [Duggan, 1990] [Aveni, 1977] 0 Weapon availability 0 Perception of own * Curiosity [Berk, 1974] [ Berkowitz, 1964] strength/self-efficacy * Political events * Opposition [Canetti, 1981] [ Bandura, 1977] [Sullivan, 1977 0 Knowledge visibility * Time stress [Berk, 1974] [ reactions/motives " Making a statement [Berk, 1974] [Fogelson, 1971] 0 Age [Russell, 1998] " Proximity to speaker & Physically Aggressive [Meyer, 1978] [Russell, 1998] • Racial event [Weller, 1985] [Russell, 1995] • Frustration [Berk, 1974] 0 Underemployment [Dollard, 1947] [Russell, 1995] * Potential for reward 0 Commitment to cause [Berk, 1974] [ [Berk, 1974] * Time of day [Stark, 1972] [Stark, 1974] * Homogenity [Feinberg, 1988] [ Derlega, 2002] " Convenience [Aveni, 1977] * Comfort [Aveni, 1977] * Self efficacy [Bandura, 1977] This perspective is more of a process than an entity and provides a useful taxonomy for summarizing the literature. A sampling of relevant psychological variables that have been examined in the crowd context can be related to each of these phases.…”
Section: Assembling Gathering Dispersalmentioning
confidence: 99%
“…However, an interdependent self-construal (particularly the aspect of relatedness) has been found to be connected to participants' willingness to adopt more constructive conflict resolution strategies (such as compromises and integration attempts; Derlega, Cukur, Kuang, & Forsyth, 2002;Oetzel, 1998). Furthermore, Karremans, Van Lange, and Holland (2005) found that self-reported relatedness to other people was associated with a higher willingness to forgive.…”
Section: Self-construal and Research On Social Justicementioning
confidence: 99%
“…Derlega et al, 2002;Holt and Devore, 2005;Kozan, 1997;Ting-Toomey et al, 1991). For example, Kozan and Ergin (1999) use Schwartz's individual-level values survey to demonstrate that employees of 40 Turkish organizations who valued tradition, security, and conformity were more likely to embrace an avoiding style of conflict management.…”
Section: The Relationship Of Humankind To the Natural And Social Worldmentioning
confidence: 99%